Budaya Organisasi, Komitmen Profesional, Dan Etika Auditor Terhadap Kinerja Auditor - Vindi Slamet Sesari; Ahmad Mukoffi; Hermi Sularsih; Fidyah Arini Kusuma Wardhani (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to examine the effect of organizational culture, professional commitment, and auditor ethics on the performance of auditors at the Surabaya public accounting firm. The type of research conducted is descriptive quantitative research with survey method. The number of respondents in this study were 60 respondents from 12 Public Accounting Firms in Surabaya which were selected randomly. The method of data acquisition comes from questionnaires that are distributed directly to respondents. The data analysis technique used multiple linear regression analysis and hypothesis testing using the determinant coefficient test, t-test, and f-test. The results of the study indicate that organizational culture, professional commitment, and auditor ethics have a significant influence on auditor performance.